Financing of public private partnerships: Transactional evidence from Australian toll roads - Regan, M.; Smith, J.; Love, Peter (Elsevier Ltd, 2017)
© 2017 World Conference on Transport Research Society In the past fifteen years, Public Private Partnerships (PPPs) have emerged as the preferred procurement method for toll road construction and management in developed economies. In Australia, seven of eight new toll roads implemented since 2003 were commissioned as PPP projects. Unlike traditional procurement methods, PPPs involve higher levels of risk for private firms, who rely on bank loans for up to 85% of development funding. This study undertakes a comparative review of the financing of six of these projects of which two were financed after the global financial crisis of 2008. The review considers matters such as capital formation and structure, risk allocation, loan tenors, and the organisation of equity. Common characteristics are also identified including the use of short-term bank debt, reform of State PPP policy, forecasting error and the financial failure of projects, and changes in risk allocation over the 10 years of the survey. With one exception, projects were delivered on, or ahead of budget, and on time. However, two projects experienced financial failure and substantial loss of asset value. Moreover, a further project traded for nine years before it was sold at less than half of its original construction cost. The paper identifies lessons learnt from recent toll road experience in Australia and recent policy reforms particularly in the area of risk allocation are examined.